Gümrük Birliği “Anlaşması”nın 1/95 Sayılı Ortaklık Konseyi Kararı’nın Hukuksal Niteliği - Kemal Başlar (Ankara Avrupa Çalışmaları Dergisi)
In the (former) candidate countries, the decisions of Association Councils havebeen construed as a kind of treaty. In most cases, they have been either promulgated bya governmental decree or published in official gazettes. All the same, the decisions ofthe EC-Turkey Association Council, established by the Ankara Agreement of 1963, arenot generally viewed as a treaty (i.e. agreement or memorandunı of understanding).Neither is it counted on as an act of government so as to subject to judicial review. Noconcrete answer has been giyen hitherto to the question as to the legal status of theAssociation Council decisions in Turkey. In the midst of uncertainties, this articleendeavours to look at the legal nature of Association Council decisions per se and the1195 Association Council Decision in particular.The 1195 Decision establishing a customs union between EC and Turkey wasneither approved of by Parliament nor ratified by President. Corollary, it was notpublished in the Official Gazette. This article argues that the 1/95 Customs UnionDecision should have been put into force by way of the procedure laid down in Article90 of the Turkish Constitution. As having not been done as such, - the author opinesthat - it is an unconstitutional document which must be declared as null and void.This article casts light on the case law of the Council of State and theConstitutional Court to see if there is any likelihood that the 1/95 Decision be declaredby the said Courts as having no legal validity in domestic law.